2007
DOI: 10.1590/s1806-37132007000100014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da participação de pequeno número de estudantes universitários em um programa de tratamento do tabagismo

Abstract: Among the university students evaluated, there was a phase, classified as precontemplative or contemplative, during which they were refractory to smoking cessation. Although all of the students were aware of the diseases caused by smoking, 41.5% did not consider themselves addicted. The concept of substance dependence does not apply to these students. It would seem more appropriate to define nicotine dependence as resulting from the lifetime consumption of at least 100 cigarettes. These students do not perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
0
5
0
11
Order By: Relevance
“…Nestes casos, as estratégias devem ser direcionadas a promover a motivação para que esses indivíduos parem de fumar, pois o tratamento do tabagismo só será efetivo quando o fumante estiver mobilizado para realizar mudança em seu comportamento (15,16) . Aqueles que afirmam que pretendem parar de fumar nos próximos meses se encontram na fase de ação e, portanto, deveriam receber uma atenção especial dos profissionais da saúde, levando em consideração esta motivação e por estarem num ambiente de ensino e saúde.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Nestes casos, as estratégias devem ser direcionadas a promover a motivação para que esses indivíduos parem de fumar, pois o tratamento do tabagismo só será efetivo quando o fumante estiver mobilizado para realizar mudança em seu comportamento (15,16) . Aqueles que afirmam que pretendem parar de fumar nos próximos meses se encontram na fase de ação e, portanto, deveriam receber uma atenção especial dos profissionais da saúde, levando em consideração esta motivação e por estarem num ambiente de ensino e saúde.…”
Section: Resultsunclassified
“…Esta determinação é também imprescindível para que o fumante vença as barreiras do processo de abandono do cigarro, que muitas vezes é longo e difícil, e com possibilidades de recaídas (17) . Em outros estudos as razões para manter o consumo do tabaco incluíram sentir prazer, sentir-se bem, aliviar tensões/estresse, não engordar, ansiedade e depressão (15,18) . Os problemas de saúde relacionados ao tabaco foram apontados como um dos principais motivos para que os fumantes deste estudo cessassem o tabagismo, similar a resultados encontrados na literatura (2) .…”
Section: Resultsunclassified
“…It is possible to imply that abandonment among young people may have occurred because they still did not feel "sick", and thought that the harmful effects of smoking would take a long time to appear, such that they would still have plenty of time to decide when to quit definitively. 28 Studies on licit and illicit drug users have reported that the younger the users are, the lower the chances are that they will remain in treatment. 29 The degree of success of and adherence to treatment among young individuals presenting substance abuse depends on variables such as severity of dependence and motivation to change behavior, among other things.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of educational measures to prevent tobacco consumption there are the research Spiandorello and collaborators; 74 Silva and collaborators…”
Section: Harmful Effects Of Smoking and Educational Measuresmentioning
confidence: 99%
“…The issue is related to the fact that they can hardly be seen as potential carriers of diseases generated by tobacco consumption. 79 Considering smoking among young people, Rodríguez and Londoño 76 conducted an experimental study in Colombia with students who wanted to give up this habit. To do this, they set up an intervention program of working level measures of consumer expectations and motivations.…”
mentioning
confidence: 99%